The development of rainfall intensity- duration- frequency (IDF) curves in klang valley - Nur Atikah, Mohammad Zulkifli (2016)
Changing in climate is one of the main parameter that affecting the water resources as it affects the whole hydrologic cycle thus causes variation in rainfall intensity, duration and frequency of precipitation. The rainfall Intensity Duration Frequency (IDF) curves relationship is one of the tools that are commonly used in water resources engineering, either for planning, designing and operating the water resources project. Department of Irrigation and Drainage (DID) is a responsible department to produce IDF curve and published as a guideline for Urban Storm water Management Manual (MSMA2). But this IDF curves use outdated data from 1990 until 2010 which is not up to date data. This IDF curves need to be update from time to time in order to ensure the IDF curves still relevant as reference. This study’s purpose is to develop IDF and also to determine the appropriate frequency analysis for every district in Klang Valley based on latest data. There were two methods used in this study such as Gumbel and Log-Normal distribution. IDF curve requires Annual Maximum Series (AMS) rainfall data from the period of 5 minutes to 7200 minutes starting from year 1990 to year 2015 for 18 stations in Klang Valley. To designing the IDF curve, process involved are mean, standard deviation, frequency factor, and intensity value for 2, 5, 10, 20, 50 and 100 year return period for both methods. The Kolmogorov-Smirnov (KS) was used in goodness of fit test to determine the appropriate frequency analysis in Klang Valley. Gumbel distribution showed to fit the graph than Log-Normal by not rejecting the value above 85% than 54 tests involve for both methods. Thus, Gumbel disribution is an appropriate method that can be use in developing the IDF curves for districts in Klang Valley than Log-Normal. Comparison between the constructed IDF curves and the existing IDF curve provided in MSMA2 had been made with range +96.55% of difference at minutes 15 at duration 100 years ARI and -52.63% of difference at minutes 1440 with duration 2 years ARI.